2018
DOI: 10.1111/ssqu.12540
|View full text |Cite
|
Sign up to set email alerts
|

What Are Good‐Looking Candidates, and Can They Sway Election Results?*

Abstract: Objective In this article, we address two major gaps in the understanding of the relationship between candidate attractiveness and electoral success. With the assistance of the Victoria Police Criminal Identification Unit in Melbourne, Australia, we show how good‐looking candidates look like by building the faces of six “ideal candidates” in terms of physical attractiveness. Utilizing our “ideal candidates,” we then investigate whether candidate attractiveness can actually sway electoral results. Methods We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Furthermore, consistent with our proposed study hypothesis 3, attractiveness was revealed to have a significant positive relationship with quality (β = .361, t = 3.568, p = .001). Attractiveness as a significant predictor and influencer of voters' candidate preference is amplified and well established in prior study findings (Banducci, Karp, Thrasher, & Rallings, 2008;Milazzo & Mattes, 2016;Nisbett & Dewalt, 2016;Praino & Stockemer, 2019). This study outcome presupposes that, physically attractive candidates are more likely to be perceived as worthy and replete with leadership values and qualities.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, consistent with our proposed study hypothesis 3, attractiveness was revealed to have a significant positive relationship with quality (β = .361, t = 3.568, p = .001). Attractiveness as a significant predictor and influencer of voters' candidate preference is amplified and well established in prior study findings (Banducci, Karp, Thrasher, & Rallings, 2008;Milazzo & Mattes, 2016;Nisbett & Dewalt, 2016;Praino & Stockemer, 2019). This study outcome presupposes that, physically attractive candidates are more likely to be perceived as worthy and replete with leadership values and qualities.…”
Section: Discussionmentioning
confidence: 58%
“…This is so because the results of a study conducted by Berggren, Jordahl and Poutvaara (2010) on 1929 Finnish political candidates from 10,011 respondents, revealed that an increase in the measure of attractiveness by one standard deviation is associated with an increase of 20% in the number of votes for the average non-incumbent parliamentary candidate. Similarly, a study by Praino and Stockemer (2018) found that approximately 75% of borderline competitions would generate a diverse winner if the genuine loser appeared like the preferred challenger and, each borderline competition would yield a different result if the loser looked like the 'perfect challenger' and the winner was very unappealing. This study suggests that candidate attractiveness can influence electoral outcomes in a competitive election.…”
Section: Putting Candidate Attractiveness In Perspectivementioning
confidence: 93%
“…We follow earlier work in having photographs judged by raters from another country (Antonakis and Dalgas 2009;Berggren et al 2010;King and Leigh 2009;Lawson et al 2010;Praino and Stockemer 2019;Praino et al 2014;Rule et al 2010;Stockemer and Praino 2017). Specifically, ratings were provided by Amazon Mechanical Turk (MTurk) workers from the U.S. Ratings by outsiders make for a cleaner and unbiased measurement of the desired traits (see Lawson et al 2010 for a discussion).…”
Section: Data Collectionmentioning
confidence: 99%
“…Since voters can only choose among the candidates in their respective district, an effect of looks implies that better-looking candidates should win more votes relative to their competitors in the district, and the size of this effect should be proportional to the size of the appearance advantage: if all candidates in the constituency are good looking, the effect on vote choice should be small; if one candidate stands out from the rest, the effect on vote share should be large (a 'frog pond' effect; see Rosar et al 2008). Consequently, we choose a statistical approach that identifies the effect of looks by comparing only those candidates that a voter actually faces, that is: we do not compare candidates from different districts (for similar strategies, see Antonakis and Dalgas 2009;Berggren et al 2010;Lutz 2010;Praino and Stockemer 2019;Praino et al 2014;Todorov et al 2005).…”
Section: Identifying the Effect Of Candidate Looksmentioning
confidence: 99%
See 1 more Smart Citation